Evaluation of coating adhesion using a radial speckle interferometer combined with a micro-indentation test - Tendela, Lucas Pedro (2012)
This paper presents a technique to investigate coating adhesion which combines a radial in-plane speckle interferometer and a micro-indentation test. The proposed technique is based on the measurement of the radial in-plane displacement field produced by a micro-indentation introduced on the coated surface of the specimen. Using steel specimens coated with a thin coating of epoxy paint and subjected to different adhesive conditions, it is demonstrated that digital speckle pattern interferometry can be successfully used to measure the small local deformations generated by a micro-indentation. An empirical model, which allows to quantify the adhesion of a given coated-substrate system by the proposed combined technique, is finally presented.